Effectiveness of balloon therapy versus incentive spirometry in promotion of respiratory function in children with lower respiratory tract diseases in selected hospitals Lucknow, Uttar Pradesh - Tiwari, Sukriti; Yadav, Jyoti; Das , Sebi (International Journal of Contemporary Pediatrics, 2024)
Background: Lower respiratory tract infections (LRTIs) are one of the most common infections that affect children’s respiratory systems it develops when the lung, specifically the lower airways become infected. The present study aims that breathing exercise helps to strengthen the children’s lungs and help to reduce the severity of respiratory sign and symptoms. So, balloon breathing exercises will be more acceptable among children. Methods: A quasi-experimental study was conducted among 60 children diagnosed with LRTI at selected hospitals, Lucknow by using a convenient sampling technique. The clinical respiratory score scale (CRS), PedsQL (Multidimensional fatigue scale) was used to measure respiratory parameter and level of fatigue. Written permission was obtained from the authorities of Balrampur hospital and Vivekananda polyclinic and institute of medical sciences, Lucknow where the study was conducted. Results: Data were analyzed by using descriptive and inferential statistics. All p values less than 0.05 were treated as significant.0.83±0.61 of the children in the experimental group and 0.93±0.88 in the control group and a p=0.536. This illustrates that overall CRS had no significant difference and results of comparison of the experimental and control group -4.0625±6.86765, -4.0517±3.93027 respectively. P=0.994 which is not statistically different. Conclusions: The study concluded that as per the present research study data, balloon therapy was found to be effective. Hence, the present research hypothesis (H1, H2, H3) is accepted.